Chapter Approccio scientifico e questioni di metodo nello studio delle scritture cirilliche - Lomagistro, Barbara (Biblioteca di Studi Slavistici, 2018)
The paper aims to formulate a scientific method for the analysis of cyrillic writing, exclusively based on the morphological features of the script. It discusses the weak points of the traditional classification of the different types of cyrillic script as ustav, poluustav and skoropis'. By refusing the use of non paleographic principles (such as orthographic ones, with or without ethnic labels), a new method is developed, based on the morphological features of each different patterns of cyrillic script, and taking into account the functional destination of the writing as well.